The new wave of foreign policy activism in turkey: Drifting away from Europeanization? - Ziya Öniş (Danish Institute for International Studies (DIIS), 2009)
Currently, the prospects for Turkey's EU membership do not look very bright. With key chapters for negotiation already suspended, the government is likely to resume a loose Europeanization agenda. The counterpart of this in the foreign-policy realm is an approach based on 'soft Euro-asianism'. An attempt is also being made to development friendly relationships with all neighboring countries, coupled with a mediating role in regional conflicts, but without the EU providing the main axis for foreign policy. The present report investigates the continuities and ruptures in Turkish foreign policy during the post-2002 AKP era. It attempts to identify the underlying reasons for the decline in enthusiasm for EU membership following the golden age of Europeanization and reforms during the early years of the AKP government. The report also points to internal and external political developments which may help to reverse the current drift away from Europeanization.
Keywords: 300; Außenpolitik; Internationale Beziehungen; EU-Erweiterung; Türkei; EU-Staaten